Muslim Entrepreneurship Transformation in the Era of Artificial Intelligence: Analysis of Opportunities and Challenges Based on Sharia Maqashid - Afdhol Rinaldi; Dhiya Dwi Afifah (MUI Kota Pekanbaru, 2026)
The rapid development of Artificial Intelligence (AI) has brought significant transformations in various business sectors, including Muslim entrepreneurship. This research aims to analyze the opportunities and challenges of Muslim entrepreneurial transformation in the AI era based on the perspective of Maqashid Sharia. Using a qualitative method with a literature review approach (library research), this study examines various academic publications, international journals, and secondary sources related to the integration of AI in sharia business and digital Islamic ethics. The results of the study show that AI offers great opportunities for Muslim entrepreneurs in improving operational efficiency, business transparency, and competitiveness of the global halal market. However, significant ethical challenges arise related to algorithm bias, data privacy, accountability of autonomous systems, and sharia compliance. The Sharia Maqashid framework that includes the protection of religion (ḥifẓ al-dīn), the soul (ḥifẓ al-nafs), reason (ḥifẓ al-ʿaql), heredity (ḥifẓ al-nasl), and property (ḥifẓ al-māl) provides a holistic ethical foundation to guide the development of responsible AI in the context of Islamic entrepreneurship. The study recommends multidisciplinary collaboration between scholars, technology developers, and regulators to ensure ethical, sustainable, and aligned adoption of AI with Islamic principles.